2017
DOI: 10.3389/fgene.2017.00079
|View full text |Cite
|
Sign up to set email alerts
|

LMNA Sequences of 60,706 Unrelated Individuals Reveal 132 Novel Missense Variants in A-Type Lamins and Suggest a Link between Variant p.G602S and Type 2 Diabetes

Abstract: Mutations in LMNA, encoding nuclear intermediate filament proteins lamins A and C, cause multiple diseases (‘laminopathies’) including muscular dystrophy, dilated cardiomyopathy, familial partial lipodystrophy (FPLD2), insulin resistance syndrome and progeria. To assess the prevalence of LMNA missense mutations (‘variants’) in a broad, ethnically diverse population, we compared missense alleles found among 60,706 unrelated individuals in the ExAC cohort to those identified in 1,404 individuals in the laminopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 97 publications
0
17
1
Order By: Relevance
“…However, since there were no chromosomal deletions on SNP arrays and exome sequencing, and none of the other genes with rare homozygous variants in the affected sisters has a known association with intellectual impairment (online supplementary table S1), there is a strong likelihood that the homozygous p.R545H LMNA mutation caused developmental delay. The arginine residue at position 545 lies in the immunoglobulin fold of globular tail domain (residues 436–552) of lamins A and C 15–17. Such immunoglobulin folds are known for protein-protein interaction, which could be disrupted with the substitution of arginine for histidine at position 545.…”
Section: Discussionmentioning
confidence: 99%
“…However, since there were no chromosomal deletions on SNP arrays and exome sequencing, and none of the other genes with rare homozygous variants in the affected sisters has a known association with intellectual impairment (online supplementary table S1), there is a strong likelihood that the homozygous p.R545H LMNA mutation caused developmental delay. The arginine residue at position 545 lies in the immunoglobulin fold of globular tail domain (residues 436–552) of lamins A and C 15–17. Such immunoglobulin folds are known for protein-protein interaction, which could be disrupted with the substitution of arginine for histidine at position 545.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study based on the analysis of variant frequencies in several public databases gathering data on 60, 706 unrelated individuals, revealed an unexpected high number of LMNA variants (n = 132), including novel variants predicted to perturb lamin A assembly or function. Among them, the variant p.Gly602Ser was identified as a potential risk factor for type 2 diabetes mellitus in African Americans [22].…”
Section: Discussionmentioning
confidence: 99%
“…We found that progeria-associated deletions either abolished (Δ50) or greatly reduced (Δ35) lamin A modification by OGT in vitro. Interestingly, three missense variants that perturb metabolism are located in the ‘sweet spot’: p.G602S (insulin resistance syndrome [ 8 ]; type 2 diabetes [ 76 ]), p.G631D (metabolic syndrome; [ 12 ]), and p.R644C (multiple phenotypes; [ 77 ]). Variant p.L92F, identified in an obese patient with severe metabolic syndrome [ 13 ], adjoins the reported O -GlcNAc site at T91 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%